Does index options trading destabilize Indian stock market volatility: an application of ARCH and GARCH models - Komal Bhardwaj; Garima; Habtamu Regassa Lemma; Matewos Kebede Refera (Cogent Business & Management, 2024)
Many investors and financial managers are interested in derivatives, which are financial instruments that derive their value from an underlying asset. These instruments have become popular due to their low initial requirements for futures trading and the need to pay premiums for options. The aim of this research, then, was to examine how the inclusion of Nifty index options impacts underlying market volatility using ARCH and GARCH models. The data set used in this study consists of 5996 time-series observations of NSE Nifty index closing prices. Here, the observations span from November 7, 1994, to December 31, 2018. Of these, 1622 observations are from the period before the introduction of options trading, while the remaining 4374 observations are from the period after the introduction of options trading. To determine the robustness of the study, the ARCH family has been chosen in order to capture the volatility behaviour and accommodate for heteroscedasticity in the returns. The coefficient's negative sign suggests that the introduction of index options has a stabilised effect on underlying market volatility, even when taking into account structural breaks.
Keywords: 650; GARCH; Business; Management and Accounting; destabilize; Economics; Finance; GARCH; Options trading; volatility